A marginalizacao que a privatizacao promove - Novelli, Pedro Geraldo Aparecido [UNESP] (My University, 2011)
When people are put aside in the society we have what is called as social marginalization. However there is a wider or even severe marginalization, i. e., the state marginalization, which is the difficulty of the citizen to recognize himself in the state. What is intended here is to identify the main features of such marginalization, its effects upon the state itself and the possible means to overcome it. In order to fulfill this aim it is taken what it is considered to be a meaningfull manifestation of the state marginalization, that is the privatization of public services. These services are usually free but it does not mean that they cost nothing because they are granted by the payment of taxes and so can be at the disposal of everyone. When these services are dealt by the private initiative then a barrier is build and many can only continue to have what should be their right if they pay more than they already do with the taxes. As an example of it we have the privatization of many highways in the state of São Paulo. A certain comunity reacted towards it but all the questions were dismissed AURORA ano V número 9 - DEZEMBRO DE 2011 ISSN: 1982-8004 http://www2.marilia.unesp.br/revistas/índex.php/aurora/. 166 by the authorities as something impossible to solve. The contradictions between the private and the public interests were solved by the legal formality but they show themselves to be expression of arbitrariness and indetermination. One comes to the conclusion that the privatization is the identification of the State with the bourgeois and civil society that turns the public thing into a private thing. Despite of all this and also because of all this the recovered knowledge about the meaning of the State and the exposition of this new marginalization may promote an ongoing striving towards a necessary mobilizing process.

Quando pessoas são postas à margem da sociedade tem-se o fenômeno conhecido como marginalização social. No entanto, há uma outra forma de marginalização, ainda maior ou mais grave, que é a marginalização estatal ou a dificuldade de se reconhecer no Estado ao qual se pertence. Nesse sentido o que se pretende é considerar as características dessa marginalização, suas implicações para o Estado e possíveis ações de sua superação. Para tanto, toma-se aqui o que se considera ser uma expressão significativa da marginalização estatal, isto é, a privatização dos serviços públicos. Estes se determinam pela sua gratuidade muito embora não sejam gratuitamente garantidos, pois é através da arrecadação de impostos que são oferecidos a todos. Na medida em que esses serviços são gerenciados pela iniciativa privada cria-se uma barreira que promove a exclusão de muitos que para continuarem a usufruir dos referidos serviços precisarão pagar algo mais além dos impostos. Exemplo dessa exclusão é a privatização de inúmeras rodovias no estado de São Paulo. A reação em uma dada localidade foi deflagrada e todas as investidas na direção da garantia de um direito público foram debeladas pelas autoridades como impossibilidades. As contradições entre os interesses privado e público são resolvidas pela formalidade legal e se apresentam como manifestações do arbitrário e do indeterminado. A conclusão a qual necessariamente se chega é que a privatização promove a submissão do Estado aos ditames da sociedade civilburguesa fazendo com que a coisa pública se transforme em coisa de alguns. Apesar disso e precisamente por isso o reconhecimento da instituição do Estado enquanto tal pode se constituir em meio de mobilização e de exposição desse novo tipo de marginalização.
Keywords: Direito; Estado; Filosofia